2022
DOI: 10.1002/advs.202202542
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐Supporting Enzyme‐Mimic Nanoscaffold Facilitates Tendon Regeneration Based on a Mitochondrial Protection and Microenvironment Remodeling Strategy

Abstract: Tendon injury is a tricky and prevalent motor system disease, leading to compromised daily activity and disability. Insufficient regenerative capability and dysregulation of immune microenvironment are the leading causes of functional loss. First, this work identifies persistent oxidative stress and mitochondrial impairment in the regional tendon tissues postinjury. Therefore, a smart scaffold incorporating the enzyme mimicry nanoparticle‐ceria nanozyme (CeNPs) into the nanofiber bundle scaffold (NBS@CeO) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…28−30 Hydrogen peroxide (H 2 O 2 ) is an essential ROS agent and serves as the source of many other radical species in tendon injury. 5,9 1K,L, S3, and S4). Thus, the Ru doping endowed the nanoparticles with efficient H 2 O 2 scavenging activity (Figure 1J).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28−30 Hydrogen peroxide (H 2 O 2 ) is an essential ROS agent and serves as the source of many other radical species in tendon injury. 5,9 1K,L, S3, and S4). Thus, the Ru doping endowed the nanoparticles with efficient H 2 O 2 scavenging activity (Figure 1J).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is an essential ROS agent and serves as the source of many other radical species in tendon injury. , CAT can decompose H 2 O 2 into H 2 O and O 2 , which is a crucial kind of enzyme in biological redox equilibrium maintenance. , Consequently, we examined the CAT-mimetic activity of ENs by monitoring the scavenging of H 2 O 2 and the generation of O 2 . The ENs show a high H 2 O 2 elimination rate with 90.9% decomposition of H 2 O 2 in the first 5 min, whereas the Zn-NCs could not eliminate H 2 O 2 (Figure H). Simultaneously, the evaluation of the generation of O 2 showed that ENs quickly and thoroughly decomposed H 2 O 2 into O 2 and H 2 O (Figure I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotator cuff injury is a common disease in sports medicine, which has a great impact on shoulder joint function . Blood supply interruption after tendon injury results in a difficult recovery process due to the low vascularity of the tissue. , Immune microenvironments are also critical to the formation of tissues in osteoimmunology . It is beneficial for tissue healing when macrophages polarize to the M2 phenotype. , In the case of tendon injury, the bone defect may cause the refixed tendon-bone enthesis to retear again. , As a result, the key for rotator cuff tissue repair is to promote the regeneration of the tendon vascular tissue, regulate the immune microenvironment, and strengthen the stability of the tendon-bone enthesis.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Immune microenvironments are also critical to the formation of tissues in osteoimmunology. 4 It is beneficial for tissue healing when macrophages polarize to the M2 phenotype. 5,6 In the case of tendon injury, the bone defect may cause the refixed tendon-bone enthesis to retear again.…”
Section: ■ Introductionmentioning
confidence: 99%